Enhanced photovoltaic performance of ultrathin Si solar cells via semiconductor nanocrystal sensitization: energy transfer vs. optical coupling effects. Issue 11 (18th December 2015) - Hoang, Son; Ashraf, Ahsan; Eisaman, Matthew D.; Nykypanchuk, Dmytro; Nam, Chang-Yong
Abstract : Efficient energy transfer from semiconductor nanocrystals, combined with optical coupling effects, enhances the efficiency of ultrathin Si solar cells by up to 45 percent. Abstract : Excitonic energy transfer (ET) offers exciting opportunities for advances in optoelectronic devices such as solar cells. While recent experimental attempts have demonstrated its potential in both organic and inorganic photovoltaics (PVs), what remains to be addressed is quantitative understanding of how different ET modes contribute to PV performance and how ET contribution is differentiated from the classical optical coupling (OC) effects. In this study, we implement an ET scheme using a PV device platform, comprising CdSe/ZnS nanocrystal energy donor and 500 nm-thick ultrathin Si acceptor layers, and present the quantitative mechanistic description of how different ET modes, distinguished from the OC effects, increase the light absorption and PV efficiency. We find that nanocrystal sensitization enhances the short circuit current of ultrathin Si solar cells by up to 35%, of which the efficient ET, primarily driven by a long-range radiative mode, contributes to 38% of the total current enhancement. These results not only confirm the positive impact of ET but also provide a guideline for rationally combining the ET and OC effects for improved light harvesting in PV and other optoelectronic devices.